2023
DOI: 10.1039/d2im00037g
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in non-fused ring electron acceptors for high performance organic solar cells

Abstract: The recent progress in non-fused ring electron acceptor-based organic solar cells has been reviewed from the perspective of material design strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 97 publications
1
32
0
Order By: Relevance
“…38,39 Considering the crucial role of morphological stability in the stability of the final device, the excellent stability of multidimensional NFAs based OSCs may partially originate from their potentially robust 3D packing network formed not only by the strong intermolecular p-p stacking but also by the weak noncovalent interactions. 26,27,40…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…38,39 Considering the crucial role of morphological stability in the stability of the final device, the excellent stability of multidimensional NFAs based OSCs may partially originate from their potentially robust 3D packing network formed not only by the strong intermolecular p-p stacking but also by the weak noncovalent interactions. 26,27,40…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…Recent literature on the OPV cell technology corroborates the efficiency rates reported by NREL. For example, recent review studies conducted by Li Y. et al 158 and H. Gao et al 159 reported that the latest developments in OPV cells have achieved a PCE% of up to 18.6% and an FF% of approximately 80%. These findings are consistent with the data presented in NREL's report.…”
Section: Organic Pv Cellsmentioning
confidence: 99%
“…Currently, the PCEs of devices based on NFRAs have reached in the range of 15–16 %, [66–68] and approaching the values attained by A‐D‐A type A7‐based FRAs. Although the PCE of the NFRA‐based OSCs is increasing rapidly, compared with the performance of FRAs, the NFRAs still have a large scope for development and were recently reviewed under different perspectives [69–73] …”
Section: Introductionmentioning
confidence: 99%